PENGARUH PEMAHAMAN SELF ASSESSMENT, SANKSI PAJAK, KESADARAN PAJAK SERTA KUALITAS PELAYANAN FISKUS TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Pada Kantor Pelayanan Pajak Pratama Kota Pangkalpinang Tahun 2013-2018) - Suherly, Friandy; Tri Setyo Mulyani, Hendarti; Astuti, Nelly (Jurnal Akuntansi Bisnis Dan Keuangan, 2019)
This research is motivated by the low level of compliance with paying taxes. The purpose of this study was to determine the effect of understanding self-assessment, tax sanctions, tax awareness and quality of tax authorities services on individual taxpayer compliance both partially and simultaneously. This research was conducted at the KPP Pratama in Pangkalpinang City. The population in this study is an individual taxpayer registered at KPP Pratama, Pangkalpinang City. Sampling is done by simple random sampling method. The number of samples is determined by 100 people from the number of individual taxpayers. Data sources in this study use primary data with quantitative methods. Data collection techniques used survey methods with media questionnaires. The data analysis technique used is multiple linear regression analysis techniques. The results of partial hypothesis testing show that understanding self-assessment, tax sanctions, tax awareness and quality of tax service services have a positive effect on individual taxpayer compliance. Simultaneous hypothesis testing results show that understanding self-assessment, tax sanctions, tax awareness and quality of service of tax authorities have a positive effect on individual taxpayer compliance. With a determination coefficient of 64.2% while the remaining 35.8% is explained by other factors not examined.